THE DEVELOPMENT OF TRADITIONAL SNACK QUALITY THROUGH ENGINEERING PROCESS AND PRODUCT DIVERSIFICATION TOWARD A CREATIVE AND ADVANCED VILLAGE - Marwanti, Marwanti; Lastariwati, Badraningsih; Ekawatiningsih, Prihastuti (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2018)
The purpose of community service is 1) to improve knowledge and skill to make a standard of clean and safe snack product, 2) to diversify snack food product, 3) to expand marketing reach to optimize snack food producer potency toward a creative village of Yogyakarta City. The training was followed by the sellers who are also a snack food maker in Kampung Tegalkemuning, Tegalpanggung, Danurejan Yogyakarta. The number of participants who attended the practice was twenty-four people. The group consists of families that had traditionally produced traditional snacks which were sold every day in several snack shops, several institutions, and some hotels. The methods used in the community service activities are a) lectures and discussions on the scope of snacks, food security, packaging and marketing, b) diversification competitions of cassava-based snacks and the processed products, c) training in snacks development and expanding marketing reach. The results of the community service are that the participants enthusiastically attended the training, as most of the participants wanted to move forward and develop. The achievement of the practice is the trainees understand and able to create snack products, especially packaging, marketing and product diversification. Participants can produce quality snacks and increase turnover.